2021
DOI: 10.3389/fonc.2021.618540
|View full text |Cite|
|
Sign up to set email alerts
|

TPX2 Enhanced the Activation of the HGF/ETS-1 Pathway and Increased the Invasion of Endocrine-Independent Prostate Carcinoma Cells

Abstract: The prognosis for endocrine-independent prostate carcinoma is still poor due to its highly metastatic feature. In the present work, TPX2 (the targeting protein for Xklp2), which is known as a micro-tubulin interacted protein, was identified as a novel coactivator of ETS-1, a transcription factor that plays a central role in mediating the metastasis of human malignancies. TPX2 enhanced the transcription factor activation of ETS-1 and increased the expression of ETS-1’s downstream metastasis-related genes, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Several studies have found that a reduction in TPX2 levels is beneficial for cancer treatment. For example, the depletion of TPX2 can significantly inhibit prostate cancer and cholangiocarcinoma cell activity and migration, and TPX2 knockdown can inhibit tumor growth considerably in vivo [33][34][35]. Furthermore, the upregulation of TPX2 expression has been shown to significantly promote non-small-cell lung cancer, hepatocellular cell migration, and invasion; it has also been associated with increased cell plasticity [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that a reduction in TPX2 levels is beneficial for cancer treatment. For example, the depletion of TPX2 can significantly inhibit prostate cancer and cholangiocarcinoma cell activity and migration, and TPX2 knockdown can inhibit tumor growth considerably in vivo [33][34][35]. Furthermore, the upregulation of TPX2 expression has been shown to significantly promote non-small-cell lung cancer, hepatocellular cell migration, and invasion; it has also been associated with increased cell plasticity [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the factors that ETS-1 is not only an important regulator of human cancerous cells’ proliferation, but also enhancing the invasive ability of cells, the transwell assays were performed ( 16 , 18 , 71 ). The results were shown as the images of the invaded cells or the quantitative results of the images.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor ETS-1 (E26 transformation-specific sequence 1) is an important regulator of malignant tumor cell proliferation that also has central roles in metastasis and invasion (16)(17)(18). Some evidence indicates that ETS-1 is closely related to the progression of a variety of tumors, including breast cancer and liver cancer, and its high expression is positively correlated with the degree of tumor malignancy (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been considered a micro-tubulin interacting protein and recently has been considered an important regulator of human malignancy proliferation and metastasis [ 7 , 8 ]. Our previous publication and some other publications reported that TPX2 may also function as regulators of transcription factors (ETS-1) or nuclear receptors (androgen receptor [AR]) [ 9 , 10 ]. However, the detailed role of TPX in HCC and specifically in HCC cellular resistance to antitumor drugs is largely unknown.…”
Section: Introductionmentioning
confidence: 99%